Isolation and screening of microorganisms with potential for biotransformation of terpenic substrates - Bier,Mário César Jucoski (2011)
The objective of the present work was to isolate and select strains with potential to perform the biotransformation of terpenic substrates. Microorganisms obtained from a collection culture and also isolated from a natural source of terpene substrate were tested. Seventeen strains were selected by their resistance to terpenes in potato dextrose agar containing up to 1% of limonene or α-pinene and β-pinene (1:1). Subsequently, 10 strains were selected by their capacity of using these terpenes as sole carbon source in a mineral medium. The biotransformation capacity of these strains was tested and the products obtained were identified by GC-MS.